2019
DOI: 10.17537/2019.14.635
|View full text |Cite
|
Sign up to set email alerts
|

Analytical Design of the Human Bronchial Tree for Healthy Patients and Patients with Obstructive Pulmonary Diseases

Abstract: The study is aimed at the analytical design of the full human bronchial tree for healthy patients and patients with obstructive pulmonary diseases. Analytical formulas for design of the full bronchial tree are derived. All surfaces of the bronchial tree are matched with the second-order smoothness (there are no acute angles or ribs). The geometric characteristics of the human bronchial tree in the pathological case are modeled by a "starry" shape of the inner structure of the bronchus; the pathology degree is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…The internal cross section of the bronchi is not rigorously circular even in the nonpathological case [16,17]. A brief review of the histological structure of the bronchi can be found in [2]. It should be only noted that the internal cross section of the bronchi has a "starry" shape.…”
Section: Change In the Bronchus Shapementioning
confidence: 99%
See 4 more Smart Citations
“…The internal cross section of the bronchi is not rigorously circular even in the nonpathological case [16,17]. A brief review of the histological structure of the bronchi can be found in [2]. It should be only noted that the internal cross section of the bronchi has a "starry" shape.…”
Section: Change In the Bronchus Shapementioning
confidence: 99%
“…The function that describes the cross-sectional shape of the bronchi of healthy patients and patients with obstructive pulmonary diseases can be written in the following form [2]:…”
Section: Change In the Bronchus Shapementioning
confidence: 99%
See 3 more Smart Citations